Thermal conditions of road pavements and their influence on motor traffic - Laurinavičius, Alfredas; Čygas, Donatas (Transport, 2003)
The article presents the analysis of climatic conditions in the Republic of Lithuania and describes their influence on road asphalt concrete pavement. Dependence of the main properties of asphalt concrete mixtures on temperature is described with the help of carried out experiments. Research findings show that the probability of plastic defomations (rutting and corrugation) in asphalt concrete pavement is higher when the pavement temperature is 20–40 °C. Ptactical application of the presented conclusions and recommendations will enable to reduce the occurrence of undesirable deformations in asphalt concrete pavements and to improve traffic conditions on the roads.First Published Online: 19 Dec 2011